CircDDX17 inhibits invasive progression of pituitary adenomas by sponging miR-1279 and regulating CADM2 expression - Yue, Xiao; Lan, Fengming; Liu, Weiping (Frontiers in Oncology, 2023)
Purpose Increasing evidence has revealed that circDDX17 plays significant regulatory roles in tumor progression. In the present study, we investigated the role of circDDX17 in pituitary adenomas (PAs). Methods Reverse transcription–quantitative PCR was performed to detect the expression of Circular RNA DDX17 (circDDX17), microRNA-1279 (miR-1279), and cell adhesion molecule 2 (CADM2) in PA tissues. Cell abilities of migration and invasion were examined by wound healing and transwell assays. Dual-luciferase reporter, RNA immunoprecipitation, and RNA pull-down assays were applied to confirm the associations among circDDX17, miR-1279, and CADM2. Xenograft tumor experiments were performed to investigate the roles of circDDX17 in vivo. Results In the present study, we found that circDDX17 was downregulated in PA tissues correlated with invasion, tumor size, and progression-free survival of patients with PA. Enforced expression of circDDX17 significantly inhibited migration and invasion through miR-1279. Notably, CADM2 was verified as the direct binding target of miR-1279, and silencing the expression of CADM2 reverses the tumor suppressing effects induced by circDDX17 overexpression. We demonstrated that circDDX17 upregulated the expression of CADM2 by sponging miR-1279, which suppressed the invasive biological behaviors of PA. Conclusion CircDDX17 may serve as a tumor suppressor and potential promising biomarker and effectively therapeutic target for the management of PA.